WADAI BANJAR RAJA YANG TURUN TAKHTA - Rizki Amalia Afriana; Penta Lestarini; Muhammad Riduan Abdillah (Universitas Islam kalimantan MAB, 2019)
Wadai comes from Banjar Language, which means cake, so Wadai Khas Banjar is a typical cake from Banjarmasin City. Wadai Khas Banjar is a mainstay culinary city of Banjarmasin that needs to be maintained, because currently the existence of this Typical Banjar has been eroded by attacks from various kinds of modern cakes that offer a variety of flavors, shapes and preparations, so that the average person if faced with the choice of whether the Wadai Khas Banjar or modern cakes, they prefer modern cakes, because the variations and tastes are very diverse. For this reason, we will strive to help maintain the existence of this Banjar Typical Wadai by conducting activities including the Community Partnership Program. This program is for typical Banjar entrepreneurs who aim to increase the knowledge and competence of Banjar Typical entrepreneurs to solve problems in the field of business management and operating / production aspects in the form of profile and organizational structure, marketing strategies, working capital management and calculation of production costs and product diversity . This activity is planned to be held for 8 months effectively from April to November 2018. The target audience is businessmen and business employees of Wadai Khas Banjar. In the implementation of the activities the materials used consisted of training documents, extension modules, proofs of transactions and raw materials for the typical Banjar Wadai. Approach method for solution to problems in the form of counseling and training, employer mobilization, business management intervention and evaluation of activities of science and technology activities for the community in the form of extension, training and implementation activities in Banjar Wadai Typical business in Banjarmasin Central City District, Banjarmasin in business management and production. The output of this activity is in the form of profile and organizational structure, implementation of new marketing strategies, working capital proposals and calculation of production costs and typical Banjar Wadai products with new flavor variances and forms.Keywords: Community partnership program, Wadai Khas Banjar